The Burial of History Behind Myth: Public Perceptions of Banten’s Mystical Powers and the Decline of Historical Awareness” - Siti Khoiroh; Rama Aditiya Putra; Fuadul Umam; Fitriah; Agus Permana; Affan Ismail (Program Studi Sejarah Peradaban Islamm UIN Raden Fatah Palembang, 2026)
This article examines the decline of historical knowledge among the people of Banten, a phenomenon increasingly overshadowed by the dominance of supernatural-power myths within the collective memory. Although Banten holds a significant historical legacy through the glory of the Sultanate of Banten and its role in regional trade and political networks, the public is more familiar with sacred figures, jawara, and supernatural narratives than factual history. This study aims to identify patterns of public perception regarding supernatural power, explain the cultural factors that sustain mythmaking, and analyze their impact on historical literacy. Data were collected through literature review, field observation, in-depth interviews with traditional leaders and local communities, and documentation of cultural artifacts. The data were analyzed using content analysis and a descriptive-analytic approach supported by Halbwachs’ collective memory theory and Berger and Luckmann’s social construction theory to explain the internalization process of knowledge. The findings reveal that perceptions of supernatural power are shaped by oral traditions, local heroic narratives, and social-spiritual networks that reinforce the legitimacy of sacred figures. The dramatic, memorable, and identity-based nature of myths makes them more dominant than academic history, which is often perceived as formal and less accessible. Consequently, crucial aspects such as the political structure of the Sultanate, its economic dynamics, and its historical contributions become neglected. The study concludes that myths not only shape public perception but also weaken historical understanding. Therefore, revitalizing local history education through strengthened documentation, accessible scholarly narratives, and community involvement is necessary to balance myth and historical facht. Keyword: Banten; Myth; Supernatural Beliefs; Historical Knowledge; Cultural Perception; Banten Sultanate; Collective Memory.